Effects of Physical Exercise on Executive Function in Adults with Depression: A Systematic Review and Meta-Analysis - Contreras-Osorio, Falonn; Ramirez-Campillo, Rodrigo; Cerda-Vega, Enrique; Campos-Jara, Rodrigo; Martínez-Salazar, Cristian; Reigal-Garrido, Rafael Enrique; Hernández-Mendo, Antonio; Carneiro, Lara; Campos-Jara, Christian (IOAP-MDPI, 2022)
Executive function is among the most affected cognitive dimensions in depression. Physical exercise may improve executive function (e.g., working memory, inhibition, cognitive flexibility), although this is without consensus on adults with depression. Through this systematic review, we aim to elucidate the effects of physical exercise programs on executive functions in adults with depression. The literature search was performed in four relevant electronic databases, combining keywords and medical subject headings, from inception until September 2022. Controlled interventions, involving adults with depression, and reporting working memory, inhibition, and/or cognitive flexibility pre-post-intervention data, were considered includable. Results from meta-analyses included effect size (ES, i.e., Hedges’ g) values reported with 95% confidence intervals (95%CIs), with p set at ≤0.05. Seven studies were included, including 202 men and 457 women (age: 21.0–51.2 years; mild–moderate depression). For working memory, a small favoring effect was observed in the experimental groups compared with controls (ES = 0.33, 95%CI = 0.04–0.61; p = 0.026; I2 = 64.9%). For inhibition, physical exercise had a small favoring non-significant effect compared with controls (ES = 0.28, 95%CI = −0.17–0.74; p = 0.222; I2 = 72.4%). Compared with the control group, physical exercise had a trivial effect on cognitive flexibility (ES = 0.09, 95%CI = −0.21–0.39; p = 0.554; I2 = 68.4%). In conclusion, physical exercise interventions may improve working memory behavioral measures in adults with mild-to-moderate depression when compared with active and passive control conditions. However, the reduced number of available high-quality studies precludes more lucid conclusions
Keywords: Depresión mental; Executive function; Inhibition; Working memory; Cognitive flexibility; Mental processes; Depressive disorder; Neurocognitive disorders; Exercise